2010
DOI: 10.1007/s00259-010-1539-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic impact of 18F-FDG PET/CT in follicular lymphoma

Abstract: FDG PET/CT is useful for staging and assessing the prognosis and therapeutic response of patients with follicular lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 14 publications
5
101
0
5
Order By: Relevance
“…Thirdly, 18F-FDG-PET can be used to evaluate treatment response if a patient has 18F-FDG-avid gastrointestinal lesions. In nodal follicular lymphoma, disappearance of 18F-FDG accumulation after completion of treatment has been associated with a favorable outcome [23][24][25] . Although the cost and benefit (e.g., sensitivity, specificity, and patient acceptability) of 18F-FDG-PET vs other modalities, including the combination of CT scanning and endoscopic examinations, remains to be investigated, 18F-FDG-PET represents an option for assessing the therapeutic effect in cases of gastrointestinal involvement of follicular lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, 18F-FDG-PET can be used to evaluate treatment response if a patient has 18F-FDG-avid gastrointestinal lesions. In nodal follicular lymphoma, disappearance of 18F-FDG accumulation after completion of treatment has been associated with a favorable outcome [23][24][25] . Although the cost and benefit (e.g., sensitivity, specificity, and patient acceptability) of 18F-FDG-PET vs other modalities, including the combination of CT scanning and endoscopic examinations, remains to be investigated, 18F-FDG-PET represents an option for assessing the therapeutic effect in cases of gastrointestinal involvement of follicular lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nodal and extranodal lesions not detected by other modalities have been identified using 18F-FDG-PET, thereby resulting in a significant advance in lesion management [18][19][20][21][22] . The usefulness of posttreatment 18F-FDG-PET during the follow-up period in cases of follicular lymphoma has also been noted, with positive 18F-FDG accumulation suggesting an adverse outcome [23][24][25] . Consequently, 18F-FDG-PET is considered a valuable tool for the management of nodal follicular lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Published literature includes 10 retrospective analyses [9][10][11][12][13][14][15][16][17][18] and 1 prospective one [19]: pooled analysis of 356 patients revealed that 24% were upstaged from Stage I-II to Stage III-IV. Baseline PET also showed to have a high prognostic value, irrespective of FLIPI [10,11,17,19]. No study reported the clinical outcomes in patients in which the therapy was adjusted according to a PET-staged disease.…”
Section: Issue 1: Staging (Consensus-based Recommendations)mentioning
confidence: 99%
“…PET scanning proved to be effective in at least four major studies on large series of patients included in prospective clinical trials [Le Dortz et al 2010;Trotman et al 2011;Lopci et al 2012;Dupuis et al 2012]. MRD monitoring also proved to be a powerful outcome predictor in FL in a…”
Section: Introductionmentioning
confidence: 99%